School Leadership Styles and Their Impact on Teacher Attitudes and Job Satisfaction in Israeli High Schools - Deborah SCHWARTZ (Revista de Management Comparat International)
This paper examines relations between school leadership styles, particularly transformational and transactional leadership, and its impact on teacher involvement and job satisfaction in Israeli high schools. The research sample included 40 high school principals, 324 English teachers, and 212 parents from both Jewish and Arab sectors. Data were collected through questionnaires based on the Teaching and Learning International Survey (TALIS) framework, measuring principals' involvement, transformational and transactional leadership styles, and aspects of school management. Multiple linear regression analyses were conducted to predict teacher involvement and job satisfaction based on principal variables. Results indicated that principal's involvement and close management supervision positively correlated with teacher involvement, while principal's responsibility negatively influenced job satisfaction. However, transformational and transactional leadership styles did not show significant direct effects on job satisfaction. Subgroup analyses revealed differences among Jewish and Arab teachers, with transformational leadership negatively impacting Arab teacher involvement, contrary to its positive impact on Jewish teachers. While transformational leadership may not directly influence job satisfaction, its interaction with other variables such as cultural contexts and management practices warrants further investigation. Understanding these complexities is crucial for enhancing teacher engagement and satisfaction, ultimately benefiting student learning outcomes.